New evidence for T-cadherin in COVID-19 pathogenesis, endothelial dysfunction, and lung fibrosis - Semina, Ekaterina; Popov, Vladimir; Khabibullin, Nikita; Klimovich, Polina; Sysoeva, Veronika; Kurilina, Ella; Tsokolaeva, Zoya; Tkachuk, Vsevolod; Rubina, Kseniya (Frontiers in Cell and Developmental Biology, 2025)
The COVID-19 pandemic had an unprecedented impact on all aspects of human activity worldwide, frequently resulting in post-acute sequelae and affecting multiple organ systems. The underlying mechanisms driving both acute and post-acute manifestations of COVID-19 are still poorly understood, warranting further investigation for new targets. The study represents the first attempt to explore the role of T-cadherin in COVID-19 pathogenesis as well as its implications in pulmonary fibrosis and endothelial dysfunction. First, we revealed a significant decrease in T-cadherin expression in post-mortem lung samples from COVID-19 patients. This downregulated T-cadherin expression correlated with the elevated levels of VE-cadherin and reduced levels of β-catenin, suggesting a disruption in endothelial cell-cell contact integrity and function. Second, the reciprocal relation of T-cadherin and VE-cadherin expression was further confirmed using cultured human endothelial Ea.hy926 cells. T-cadherin overexpression caused a decrease in VE-cadherin mRNA expression in cultured endothelial cells providing additional evidence in favor of their interplay. Third, employing Cdh13−/− mice, we unveiled the protective role of T-cadherin deficiency against bleomycin-induced lung fibrosis. Fourth, we demonstrated the mice lacking T-cadherin to have downregulated reactive oxygen species production and Nox2 mRNA expression in an angiotensin II-mediated endothelial dysfunction model. Our findings provide rationale for further studies into T-cadherin-mediated mechanisms in these processes.